Gen Z generation: does job hopping matter - Kholis Nur Arifin,; Nina Fitriana,; Reny Yuniasanti, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rise of Gen Z in the workplace has become a cause for concern in the last few years for organizations because of its characteristic of changing jobs frequently, a behaviour labeled as job hopping. Job hopping creates problems for organizations due to its strong relation with a detrimental higher turnover rate. Indonesia faces its challenge as Gen Z enters the world of work with domination. Qualitative research using a phenomenological approach was conducted to explore a comprehensive explanation of the job hopping phenomenon among Gen Z employees in Indonesia. Data was collected through in-depth interviews and observations with six (6) participants. Thematic analysis using the reflexive method utilizing NVivo12 Plus software resulting diverse but coherent reasons for job hopping, including motivational forces, personality characteristics, and social media influence. There are two main processes of job hopping behaviour, with four (4) types of movement cycles. Participants have a rather positive view and perception of job hopping and are experiencing more positive impacts, both career wise and personal.